Analisis Perputaran Persediaan Dan Perputaran Piutang Terhadap Kinerja Kemampulabaan Perusahaan - Effendy, Marwan; Supriadi, Yoyon; Nyuantasari, Nyuantasari (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
Inventory turnover and accounts receivable turnover has a strong relationship in generating profitability of the company. Inventory turnover and accounts receivable tumover that will either lead to good profitability as well. The purpose of this study was to determine how the inventory turnover company, how the accounts receivable turnover company, how inventory turnover influences the profitability of the company, how the accounts receivable tumover influence the profitability, how the inventory turnover and receivables turnover influence the profitability. The research method was used a descriptive study, ratio analysis, and statistical analysis. The third analysis used to facilitate research. Based on the discussion of the research it can explain that the inventory turnover and accounts receivable tumover at PT. Hanjaya Mandala Sampoema Tbk better than the PT. Gudang Garam, Tbk. That happened a positive and significant relationship for inventory turnover profitability, positive and significant relationship occurred on account receivables tumover to the corporate profitability, and occurs a positive and significant relationship in inventory turnover and accounts receivables turnover to the profitability of the company. Keywords: Inventory Turnover, Receivables Turnover, profitability (ROA),